Dynamics of Lactate Accumulation in Human Spermatozoa during Perftoran Introduction into Hypothermic Storage Medium - Cherkashina, I. V. (Problems of Cryobiology and Cryomedicine, 2003)
There was studied the effect of a gas-transporting blood-substitute Perftoran on lactic acid content and spermatozoa motility under hypothermic storage conditions at 4Â°C. It has been demonstrated that perftoran (PF) adding into the incubation medium combined with the effect of methylxantine derivatives at the stage of complete stopping of cells gives the possibility to prolong the storage time of spermatozoa up to 120 hrs. The change of lactate content in incubation medium with PF testifies to the possibility of human spermatozoa to change for aerobic metabolism following 72 hrsâ€™ hypothermic storage.